Immediate effect of proprioceptive neuromuscular facilitation (PNF) of respiratory muscles on pulmonary function in collegiate students. - D.ANANDHI,; P.DEEKSHITHA,; V.P.R.SIVAKUMAR, (International Journal of Pharma and Bio Sciences, 2017)
Respiratory muscle strength and endurance can be improved by various. Breathing exercises which can consequently improve respiratory function. Proprioceptive Neuromuscular Facilitation is a new technique to improve the respiratory function such as Tidal Volume (TV), Inspiratory Reserve Volume (IRV), Expiratory Reserve Volume (ERV), Inspiratory Capacity (IC), Vital Capacity (VC). To find out the Immediate effect of Proprioceptive Neuromuscular Facilitation (PNF) of respiratory muscles on pulmonary function in collegiate students. A quasi experimental study with one group pre test post test design was done. A sample of 30 including both men and women, with an age group between 18 and 28 years, Asian BMI 17.5 – 27.99 (underweight to overweight) were selected . Subjects who were obese, smokers, who had lung diseases, cardiac diseases, congenital chest deformities, who had recent surgeries in chest wall, subjects on any physical training programs were excluded. Outcome measures were Pulmonary Function Test–Tidal Volume, Inspiratory Reserve Volume, Expiratory Reserve Volume, Inspiratory Capacity, Vital Capacity which were taken before and 5 minutes after giving PNF technique. Forced vital capacity (FVC) showed significant increase of mean difference of 2.5434 with p<0.05 and Inspiratory capacity(IC) also showed significant increase of mean difference of 0.266 with p<0.05 after giving Proprioceptive Neuromuscular Facilitation. Inspiratory Reserve Volume, Expiratory Reserve Volume and Peak Expiratory Flow Rate (PEFR) were also increased but did not show significant increase. Though IRV, ERV, PEFR increased, only FVC and IC improved significantly immediately (p<0.05) after PNF to respiratory muscles.